Sugar Signaling During Fruit Ripening - Durán-Soria, Sara; Pott, Delphine M.; Osorio, Sonia; Vallarino, José G. (Frontiers in Plant Science, 2020)
Sugars play a key role in fruit quality, as they directly influence taste, and thus consumer acceptance. Carbohydrates are the main resources needed by the plant for carbon and energy supply and have been suggested to be involved in all the important developmental processes, including embryogenesis, seed germination, stress responses, and vegetative and reproductive growth. Recently, considerable progresses have been made in understanding regulation of fruit ripening mechanisms, based on the role of ethylene, auxins, abscisic acid, gibberellins, or jasmonic acid, in both climacteric and non-climacteric fruits. However, the role of sugar and its associated molecular network with hormones in the control of fruit development and ripening is still poorly understood. In this review, we focus on sugar signaling mechanisms described up to date in fruits, describing their involvement in ripening-associated processes, such as pigments accumulation, and their association with hormone transduction pathways, as well as their role in stress-related responses.